An up-to-date catalogue of urinary markers for the management of prostate cancer - Brönimann, Stephan; Pradere, Benjamin; Karakiewicz, Pierre; Huebner, Nicolai A; Briganti, Alberto; Shariat, Shahrokh F (Current opinion in urology, 2020)
PURPOSE OF REVIEW: Prostate cancer (PCa) is the most commonly diagnosed cancer in men. Poor specificity and sensitivity of total PSA often results in over and sometimes underdetection/treatment. Therefore, more specific and sensitive biomarkers for the detection and monitoring especially of clinically significant PCa as well as treatment-specific markers are much sought after. In this field, urine has emerged as a promising noninvasive source of biomarkers. RECENT FINDINGS: RNA-based biomarkers are the most extensively studied type of urinary nucleic acids. ERG-Score/MiPS (Mi-Prostate Score) and SelectMDx might be considered as additional parameters together with clinical and imaging modalities to decrease unnecessary biopsies. miR Sentinel Tests could make it possible to accurately detect the presence of cancer and to distinguish low-grade from high-grade disease. In men with previous negative biopsies, PCA3 may suggest the need to repeat biopsy. SUMMARY: The definitive role of these markers and their clinical benefit needs future validation.
Keywords: Biomarkers, Tumor; Prostatic Neoplasms; biopsie; antigeny nádorové; prostata; nádorové biomarkery; nádory prostaty; Biopsy; Prostate-Specific Antigen; Humans; mužské pohlaví; analýza moči; lidé; Male; Prostate; prostatický specifický antigen; Antigens, Neoplasm; Urinalysis